2018
DOI: 10.1016/j.niox.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Redox regulation of soluble guanylyl cyclase

Abstract: The nitric oxide/soluble guanylyl cyclase (NO-sGC) signaling pathway regulates the cardiovascular, neuronal, and gastrointestinal systems. Impaired sGC signaling can result in disease and system-wide organ failure. This review seeks to examine the redox control of sGC through heme and cysteine regulation while discussing therapeutic drugs that target various conditions. Heme regulation involves mechanisms of insertion of the heme moiety into the sGC protein, the molecules and proteins that control switching be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 105 publications
1
38
0
Order By: Relevance
“…2d). In case of oxidative stress, in oxidized state of GC-1 becomes desensitized to available NO, leading to a decrease in cGMP production necessary for activation of downstream proteins and pathways 27 . As a result, preconditioning with riociguat significantly ameliorated nitro-oxidative stress in the myocardium of RioHTX animals, as evidenced by a significant decrease in nitrotyrosine immunoreactivity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2d). In case of oxidative stress, in oxidized state of GC-1 becomes desensitized to available NO, leading to a decrease in cGMP production necessary for activation of downstream proteins and pathways 27 . As a result, preconditioning with riociguat significantly ameliorated nitro-oxidative stress in the myocardium of RioHTX animals, as evidenced by a significant decrease in nitrotyrosine immunoreactivity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological relevance of oxidative stress on NO/sGC signaling and the impact on disease progression is still poorly understood. However, recently and also presented on the last cGMP meeting in 2017, it was shown that vascular SMC express a reductase (CYB5R3) turning back oxidized sGC into the native form (Shah et al 2018). More recently, it has been demonstrated that knock out of CYB5R3 in vascular SMC is linked to a hypertensive phenotype by reducing NOmediated sGC stimulation (Durgin et al 2019).…”
Section: Pgc Structure and Functionmentioning
confidence: 99%
“…On the other hand, apo-sGC β1 associates with Hsp90 much more strongly than sGC α1, which prevents the formation of heme-free and non-functional sGC heterodimer ( Dai et al, 2019 ). It is well established that oxidative stress, which plays a major role in the development of pulmonary vascular remodeling and a consequent increase of pulmonary pressure, can cause the oxidation of the sGC heme resulting in desensitization to NO signaling ( Shah et al, 2018 ). NO stimulates the insertion of heme in apo-sGC-β1, the dissociation of Hsp90 from the complex, and the association of sGC-α1 to form the active enzyme ( Ghosh et al, 2014 ).…”
Section: Heat Shock Protein 90 In Pulmonary Arterial Hypertensionmentioning
confidence: 99%